Historical and Legal Context and Significance… of Selected Roman Public Law Institutions of the Early Principate Described in Canonical Gospels of the New Testament - Kubala, Maciej Tomasz (The Biblical Annals, 2021)
The article analyses the issues in question by means of a method used in the legal sciences which in the Polish methodology is called “the historical and legal method.” It involves presentation and analysis of selected legal institutions and of their evolution in time. The following issues—identified across the pages of the Gospel—are analysed in this article: political and systemic context of evangelical events (section 1), the role of censuses in the implementation of Roman administrative and systemic principles (section 2), Roman tax law in the context of tax burdens resting on residents of Judea (section 3) and the Roman judicial procedure in the context of the trial of Jesus (section 4). In the summary the author answers the research question asked in the introduction: to what degree does the historical and legal significance of selected institutions of Roman law, inspired by the description of these institutions in canonical gospels of the New Testament, determine the contemporary understanding of the gospels themselves?